Research Progress on the Photo-Driven Catalytic Production of Biodiesel - Huang, Jinshu; Jian, Yumei; Zhu, Ping; Abdelaziz, Omar; Li, Hu (Frontiers in Chemistry, 2022)
Biodiesel considered a green, environmentally friendly, and renewable energy source is one of the most promising candidates to replace fossil fuels to supply energy for the world. The conventional thermocatalytic methods have been extensively explored for producing biodiesel, while inevitably encountering some drawbacks, such as harsh operating conditions and high energy consumption. The catalytic production of biodiesel under mild conditions is a research hotspot but with difficulty. Photocatalysis has recently been highlighted as an eco-friendly and energy-saving approach for biodiesel production. This mini-review summarizes typical photocatalysts for biodiesel production and discusses in detail the catalytic mechanism and strategies of the photo-driven (trans)esterification to produce biodiesel. The current challenges and future opportunities of photo-driven catalysis to prepare biodiesel are also outlined, in steps towards guiding the design of advanced photocatalysts for biodiesel production.